2020
DOI: 10.22201/fcpys.2448492xe.2020.241.75273
|View full text |Cite
|
Sign up to set email alerts
|

¿Qué sabemos del robo de combustible en México? Claroscuros de un delito que no cede

Abstract: <div class="page" title="Page 1"><div class="section"><div class="layoutArea"><div class="column"><p><span>El objetivo de este artículo es presentar un diagnóstico de la calidad de la información sobre robo de combustible en México en dos vertientes: la información relativa a la evolución y distribución del fenómeno, y la información relativa a las acciones estatales para combatirlo. Para ello, acudimos a tres distintas fuentes de información: </span><span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…For example, PEMEX reported that most fuel stealing is located in the country's central area. In Mexico City alone and the five adjacent states (among which are three of the seven entities that registered the most clandestine shots), 5,420 clandestine shots were recorded the last year, equivalent to 43% according to reported in [18].…”
Section: Results Of the Geographic And Social Topics Distributionmentioning
confidence: 99%
“…For example, PEMEX reported that most fuel stealing is located in the country's central area. In Mexico City alone and the five adjacent states (among which are three of the seven entities that registered the most clandestine shots), 5,420 clandestine shots were recorded the last year, equivalent to 43% according to reported in [18].…”
Section: Results Of the Geographic And Social Topics Distributionmentioning
confidence: 99%